(untitled) (Global Journal of Science Frontier Research, 2025)
Whenever the odds seem stacked against human aspirations - when economic growth looks set to remain feeble as far as the eye can see when too many countries seem destined to grow old before they become rich when climate change seems to have crossed the tipping point-it is worth remembering the distinctive virtue of our species Predictions of global doom have proliferated throughout history Yet the sky hasn t fallen for one reason human ingenuity